Fiqh, Women and Human Rights: Competing Methodologies - Ahmad, Ajmand (Studia Islamika, 2003)
This paper attempts to, firstly, examine in some depth various writers' investigations into Islam, women and human rights. Secondly, and more importantly, it attemps provide a clear conceptual framework within which to articulate a foundation for the subject in the future. Such a re-conceptualisation is necessary to anchor future attempts at law reform within an Islamic jurisprudential heritage. By re-locating the debate within the Islamic heritage, any articulation of human rights and Muslim women will have the authority of a fiqh-inspired methodology. For muslim women engaged in the struggle for human rights, such a strategy will be more successful than either employing secular "Western" feminist discourse or by claiming the right to interpret the original Islamic sources whilst ignoring fiqh history, methodology and terminology.DOI: 10.15408/sdi.v10i1.640